ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI KAKAO SAMBUNG SAMPING DI DESA SALUTIWO KECAMATAN BONEHAU KABUPATEN MAMUJU - Febrianto, Dian; Lamusa, Arifudin; Hamzens2, Wildani Pingkan S. (AGROTEKBIS, 2017)
The purpose of this study is to: (i) know the income of cocoa side grafting farming in Salutiwo Village Bonehau District Mamuju regency, (ii) determine the feasibility of cacao side grafting farming in Salutiwo Village Bonehau District Mamuju regency. Determination of respondent was done by intentionally (purposive). The total respondents farmer (sample) taken in this study of 32 side grafting cacao farmers. The analysis used in this research is revenue analysis and feasibility analysis. The results showed that cacao side grafting farming income in the village of Bonehau Salutiwo Mamuju District of Rp18.262.574,91/Ha. Cacao side grafting farm In Salutiwo Village Bonehau District Mamuju regency suitable to be running with the value of revenue cost ratio (R/C) of 2,80, which means that any expenditure of Rp100,- will generate revenue of R 280,-.Â Keywords: Cacao side grafting, income, eligibility.